Literatur Riview: Penetapan Kadar Vitamin C Pada Buah Jambu Biji, Jeruk, Dan Nanas, Menggunakan Metode Spektrofotometri Uv-Vis - Meika Hestina Putri; Putri Septiyani; Winda Aryani; Ermin Abriyani (Jurnal Ilmiah Wahana Pendidikan, 2023)
Vitamin C is a complex compound that is needed by the body which functions to help regulate or process the body's metabolism. Fruits are a source of vitamin C which can be consumed to meet the needs of vitamin C, such as guava, lime and pineapple. This study aims to determine the levels of vitamin C in guava, lime, and pineapple. using the UV-Vis Spectrophotometry method, which is a method with good efficiency for determining vitamin C levels. Based on testing, the results showed that vitamin C levels in guava were 0.12%, limes were 0.07096%, and pineapples were 4.274 ppm